RESEÑA de : Ibáñez, María José; Cuadrat, J.M.; Bielza, V.; Escolano, S.; Frutos, L.M.; Abadía, X.; Calvo, J.L.; Pellicer, F. Aspectos didácticos de Geografía. I. Bachillerato. Zaragoza : Universidad de Zaragoza, 1985 - García Solano, María Dolores (Espacio Tiempo y Forma. Serie VI, Geografía, 1990)
_